The Effect of Mandatory Carbon Disclosure on Financial Performance: Evidence From South African Listed Carbon-Intensive Companies - Thomas NYAHUNA; Mishelle DOORASAMY (International Journal of Environmental, Sustainability, and Social Science, 2023)
By concentrating on determining the effect of mandatory carbon disclosure on financial performance, the study assists corporate managers in effectively understanding the significance of carbon information disclosure and searching for enhanced ways of amplifying carbon disclosure. The paper examines the impact of mandatory carbon disclosure on the corporate financial performance of 45 Johannesburg Stock Exchange-listed cement and mining companies considered carbon-intensive entities from 2014 to 2021. This examination is based on the legitimacy theory. To attain the critical aim of the study, panel regression analysis is conducted with the assistance of SPSS 28. Financial performance was measured by return on assets, return on equity and net profit margin. Carbon disclosure was measured by carbon disclosure scores developed by Carbon Disclosure Project (CDP). The study reports that all financial performance proxies are positively and significantly related to carbon disclosure. To upsurge financial performance, the sampled companies must keep extensively disclosing carbon information in their annual reports per the mandatory expectations. Therefore, this paper provides evidence that mandatory carbon disclosure is a source of better financial performance and critical for the corporate sector to accomplish sustainability.